Profitability analysis of Ukrainian startups - Havrys, O. O.; Havrys, M. O. (ФОП Томенко Ю. І., 2023)
Currently, Ukraine's budget largely depends on international aid, but despite the difficulties, the economy must develop and one of the promising directions is the development of innovative entrepreneurship, which is aimed at creating new products, technologies and services. In this context, it is appropriate to talk about startups - organizational forms of innovative activity, newly created organizations that specialize in the development of a new product or service in conditions of extreme uncertainty.
Keywords: economic activity; startups; finance; information technology; business